The girls of Atomic City : the untold story of the women who helped win World War II - Kiernan, Denise; Campbell, Cassandra (Michigan Brillance Audio, 2013)
During World War II, Oak Ridge, Tennessee, was home to 75, 000 residents, consuming more electricity than New York City. Thousands of civilians, mostly young women, were recruited, enticed by solid wages and war-ending work. Few would guess the true nature of the work done there. That is, until the end of the war and the secret was revealed. Interviewing the women who lived it, the author captures the spirit of the times through them: their pluck, desire to contribute, and enduring courage.
Compact discs.
Duration: 13:00:00.
Read by Cassandra Campbell.
Keywords: Oak Ridge National Laboratory -- History -- 20th century; CD collection -- Nonfiction; Women employees -- Tennessee -- Oak Ridge -- History -- 20th century; Women -- Tennessee -- Oak Ridge -- Interviews; Uranium enrichment -- History -- 20th century; Official secrets -- United States -- History -- 20th century; World War, 1939-1945 -- Women -- Tennessee -- Oak Ridge; World War, 1939-1945 -- Tennessee -- Oak Ridge; Oak Ridge (Tenn.) -- History -- 20th century; Oak Ridge (Tenn.) -- Social life and customs -- 20th century; Oak Ridge (Tenn.) -- Biography; Audiobooks